Demand Shifts, Population Adjustments, and Labor Market Outcomes during the 1980s - Bound, John; Holzer, Harry J. (Journal of Labor Economics, 2000)
In this article we explore the effects of labor demand shifts and population adjustments across metropolitan areas on the employment and earnings of various demographic groups during the 1980s. We find that population shifts across areas at least partially offset the effects of these demand shifts, but less‐educated workers showed substantially lower population adjustments in response to these demand shifts. These limited supply responses apparently contributed importantly to relatively greater deterioration of employment and earnings of these groups in declining areas during the 1980s.